1984
DOI: 10.3758/bf03333794
|View full text |Cite
|
Sign up to set email alerts
|

Facial self-perception: Its relation to objective appearance and self-concept

Abstract: The ability to judge objectively the physical attractiveness of one's own face and the relation of these judgments to self-concept were assessed. Thirty white female and 34 white male college students rated the physical attractiveness of their own faces, once without viewing their faces (memory condition) and once while viewing photographs of their faces and the faces of the other same-sex subjects (photograph condition) . Self-concept was assessed by administration of the Tennessee Self Concept Scale. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…Consistent with previous studies (e. g. Pittenger and Baskett, 1984;Noles et at., 1985), controls overestimated their symmetry. This overestimation was specific to their own face, suggesting that, in contrast to BDD patients, controls are adopting a self-serving bias in their self-estimation.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Consistent with previous studies (e. g. Pittenger and Baskett, 1984;Noles et at., 1985), controls overestimated their symmetry. This overestimation was specific to their own face, suggesting that, in contrast to BDD patients, controls are adopting a self-serving bias in their self-estimation.…”
supporting
confidence: 82%
“…This overestimation of attractiveness in controls is consistent with the findings reported by Pittenger and Baskett (1984). Applying the mean rating by others as an objective measure of appearance, non-clinical students significantly overestimated the attractiveness of their own faces in both the memory and photograph conditions (Pittenger & Baskett, 1984).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…When objective ratings of physical attractiveness are correlated to self‐concept, this relationship disappears (16) or becomes negative, indicating that physical attractiveness in adolescence can have a negative effect on self‐concept (18). Findings such as these have led researchers to conclude that the judgment of physical appearance by others has much less of an effect on self‐concept than one’s own judgment (19).…”
Section: Self‐concept and Physical Appearancementioning
confidence: 99%
“…Studies have also found a significant positive correlation between subjects' ratings of own self‐perceived attractiveness and those they received from third‐party raters (Pittenger and Basket ). However, self‐ratings of physical attractiveness appear to be positively correlated with a wider range of attributes than actual physical attractiveness (Feingold ).…”
mentioning
confidence: 96%